Advanced MRI techniques in studying multiple sclerosis pathology and lesion progression - Elsarraj, Afaf (2016)
There is an intimate spatial and functional relationship between cerebral microvasculature and the neuroglial tissues. It is known that both cerebrovascular and neuroglial alterations occur in multiple sclerosis (MS), but the pathophysiological relationships between these alterations, and the functional consequences, are not well characterised in vivo. Evidence from previous literature indicates that there are subtle changes in blood brain barrier (BBB) in normal appearing white matter (NAWM) of MS. However, lesion development due to subtle BBB leakage remains unclear. Additionally, the haemodynamic alteration and microstructural changes in grey matter (GM) is a well-known feature in MS. Nevertheless, the structural and functional relevance of GM perfusion and diffusion necessitate more exploration.